High Prevalence of Metallo-β-Lactamase-Producing Enterobacter cloacae From Three Tertiary Hospitals in China - Cai, Yimei; Chen, Cha; Zhao, Mei; Yu, Xuegao; Lan, Kai; Liao, Kang; Guo, Penghao; Zhang, Weizheng; Ma, Xingyan; He, Yuting; Zeng, Jianming; Chen, Liang; et al. (Frontiers in Microbiology, 2019)
Enterobacter cloacae has recently emerged as one of the most common carbapenem-resistant Enterobacteriaceae. The emergence and spread of metallo-β-lactamase-producing E. cloacae have posed an immediate threat globally. Here, we investigated the molecular characteristics of eighty-six carbapenem-resistant Enterobacter cloacae (CREL) isolates collected from three tertiary hospitals in China between 2012 to 2016. Species identification and antimicrobial susceptibility testing were performed using a VITEK-2 system. The minimal inhibitory concentration (MIC) for carbapenems was determined using broth microdilution method. Isolates were screened for β-lactam resistance genes by PCR, and expression of ompC and ompF was determined by qRT-PCR. Genetic relatedness was performed by pulsed-field gel electrophoresis (PFGE), and selected isolates were subjected to whole-genome sequencing. Among the 86 CREL isolates, 50 (58.1%) were detected as carbapenemase producers. NDM-1 was the dominant carbapenemase (46.5%), followed by IMP-26 (4.7%) and IMP-4 (3.5%). Notably, we identified the first NDM-1 and IMP-1 co-producing E. cloacae, carrying plasmids of three incompatibility (Inc) groups, IncHI2, IncHI2A, and IncN. Most strains isolates showed decreased expression of ompC and/or ompF, and contained a broad distribution of extended-spectrum β-lactamases (ESBLs) and AmpC β-lactamases. These findings suggested that different molecular mechanisms, including carbapenemase, ESBLs and AmpC β-lactamases plus the loss of porins, have contributed to carbapenems resistance. The high-throughput sequencing demonstrated that seven blaNDM-1-harboring plasmids contained highly conserved gene environment around blaNDM-1 (blaNDM-1-bleMBL-trpF-dsbD-cutA1-groES-groEL), which could be associated with the potential dissemination of blaNDM-1. IMP-type MBL was located within a variety of integrons and usually contained various gene cassettes encoding multidrug resistance. All the CREL isolates could be divided into 60 PFGE clusters. Nineteen blaNDM-1-positive E. cloacae isolates obtained from Ningxia had the same PFGE pattern (Type 1) and were classified to ST78 in clonal complex 74 (CC74) by multilocus sequence typing (MLST) analysis. The plasmid-based replicon typing indicated that IncX3 plasmids mediated the dissemination of blaNDM-1 within these homologous strains. This is the first report on the outbreak of NDM-1-producing E. cloacae ST78 with contribution of IncX3 plasmids in northwestern China. There's an immediate need to intensify surveillance attentively to prevent and control the further spread of NDM-1 in China.